2021
DOI: 10.1002/jbm.a.37159
|View full text |Cite
|
Sign up to set email alerts
|

Black phosphorus incorporation modulates nanocomposite hydrogel properties and subsequent MC3T3 cell attachment, proliferation, and differentiation

Abstract: A promising strategy that emerged in tissue engineering is to incorporate two‐dimensional (2D) materials into polymer scaffolds, producing materials with desirable mechanical properties and surface chemistries, which also display broad biocompatibility. Black phosphorus (BP) is a 2D material that has sparked recent scientific interest due to its unique structure and electrochemical characteristics. In this study, BP nanosheets (BPNSs) were incorporated into a cross‐linkable oligo[poly(ethylene glycol) fumarate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As revealed consistently in the MTS test and live/dead stain, preferable cellular attachment and proliferation were displayed with the addition of BP into hydrogels, which is in line with the previous study. 9 The best cell behavior was detected in the OPF@BP-S group, indicating that the BP quantum dots may be most conducive to cell proliferation among BP nanosheets of different sizes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As revealed consistently in the MTS test and live/dead stain, preferable cellular attachment and proliferation were displayed with the addition of BP into hydrogels, which is in line with the previous study. 9 The best cell behavior was detected in the OPF@BP-S group, indicating that the BP quantum dots may be most conducive to cell proliferation among BP nanosheets of different sizes.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, phosphate is a major component of cell structure, 8 such as cell membranes, nucleic acid, and adenosine triphosphate, and also helps to regulate bone mineralization and bone resorption, therefore making BP an attractive 2D material in bone tissue engineering. Our previous research and other published studies have found that followed by the exfoliation and integration, BP nanosheet‐based hydrogel platform could be used to accelerate bone regeneration via a sustained supply of phosphate 9,10 . However, BP nanosheets have been reported to be cytotoxic in certain conditions, 11 limiting the further application of BP nanosheets as biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…BPs are emerging 2D layer-structured materials that possess unique physicochemical properties such as excellent photothermal conversion performance. In addition, previous studies have proved that BPs could be gradually oxidized to form a phosphate in a physiological environment, which drives biological mineralization procedures and promotes proliferation and osteogenic differentiation of BMSCs. , Based on the biological effects, BPs are usually applied to modify the surface of 3D-printed scaffolds or incorporated into hydrogels for bone defect repair. In this study, BPs were introduced to the fracture site through a new way of metal implant coating, which could lay a material foundation for the dual functions of a photothermal antibiofilm and promotion of fracture healing elicited by BPs.…”
Section: Resultsmentioning
confidence: 99%
“…In research, the addition of BPNs into a cross-linked OPF hydrogel improved the adhesion, distribution, proliferation, and differentiation of MC3T3-E1 cells. Optimal cell development was observed at BP doses up to 500 ppm [ 43 ]. In an additional research of 3D mesenchymal stem cell (MSC) preparations, Li et al [ 44 ] examined the osteogenic response of MSC spheroids by a novel combination of collagen and BP.…”
Section: Biomedical Application Of Black Phosphorus Hybrids Hydrogelmentioning
confidence: 99%